Pemberdayaan Masyarakat Desa Pasar Ngalam melalui Program Kuliah Kerja Nyata Berbasis Masjid - MS Efendi; Heny Sri Widarna Nengsi; Ayu Triani; Apit Triyani; Levy Satriani; Sartika Siti Nurhasanah; Nissrina Nuha Saleha; Ega Novita Utamy; Faisal Sinaga (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This study aims to analyze the implementation of a mosque-based community service program (KKN) in empowering rural communities. The research used a qualitative descriptive approach through observation, interviews, and documentation. The results show that the mosque-based KKN program has succeeded in empowering the community through various religious, educational, and socio-economic activities centered around the mosque. Key programs included Quran education for children, religious lectures, youth empowerment through mosque youth groups, and economic empowerment through mosque cooperatives. Challenges faced included limited participation from some community members and sustainability of programs after KKN ended. This study concludes that mosque-based KKN can be an effective model for holistic community empowerment when implemented with strong community engagement and follow-up plans.